Behind the curtain of scholarly publishing: editors in writing studies - Giberson, Greg, editor; Schoen, Megan, editor; Weisser, Christian, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Provides new and seasoned scholars with behind-the-scenes explorations and expositions of the histories of scholarly editing and the role of the scholarly editor from the perspectives of current and former editors from important publication venues within the field.--Provided by publisher.
Foreword: the shape of editorial work / Michael Spooner -- Introduction: why consider the role of editor / Megan Schoen and Greg Giberson -- The journal you have / Kelly Ritter -- Minutiae matters: on editing an independent journal / Laura R. Micciche -- Growing a community of colleagues: editing WLN: a journal of writing center scholarship / Muriel Harris -- PRE/TEXT / Victor J. Vitanza -- Getting up from a fall: five years as editor of WPA: Writing Program Administration / Alice S. Horning -- Opening spaces in writing studies: an impetus for change at composition forum / Christian Weisser -- Greater than the sum of its parts: enacting an editorial philosophy at College composition and communication / Kathleen Blake Yancey -- The University of Pittsburgh Press series: composition, literacy, culture / David Bartholomae and Jean Ferguson Carr -- Opening a new chapter: open access publishing in writing studies / Mike Palmquist -- Gatekeeper, guardian, or guide?: negotiating the dynamics of power as an editor / Michael A. Pemberton -- Reflections: edit to learn / Victor Villanueva -- Everything is rhetoric: design, editing, and multimodal scholarship / Douglas Eyman and Cheryl E. Ball -- Enculturation and scholarly editing as network coordination / Byron Hawk -- Building a field through editorial work: the case of second language writing / Paul Kei Matsuda -- Making space for diverse knowledges: building cultural rhetorics editorial practices / Malea Powell -- Won't you be my neighbor?: how to build a scholarly community / Charles Bazerman -- Afterword: on "becoming" an editor / Greg Giberson.
Keywords: Editors; Editing; Scholarly publishing; English language -- Rhetoric -- Study and teaching (Higher) -- Authorship